Evaluation and mitigation of the effects of in utero heat stress on piglet growth performance, postabsorptive metabolism, and stress response following weaning and transport. (24th August 2020) - Maskal, Jacob M; Duttlinger, Alan W; Kpodo, Kouassi R; McConn, Betty R; Byrd, Christopher J; Richert, Brian T; Marchant-Forde, Jeremy N; Lay, Donald C; Perry, Shelbi D; Lucy, Matthew C; Safranski, Tim J; Johnson, Jay S
Abstract: In utero heat stress (IUHS ) increases the energy requirements of pigs during postnatal life, and this may compound weaning and transport stress. The study objective was to evaluate and mitigate the negative effects of IUHS following weaning and transport through the provision of a nutrient-dense (ND ) nursery diet formulated to meet the greater energy requirements of IUHS pigs during the first 14 d postweaning and transport. Twenty-four pregnant gilts were exposed to thermoneutral (TN ; n = 12; 17.5 ± 2.1 °C) or heat stress (HS ; n = 12; cycling 26 to 36 °C) conditions for the first half of gestation (day 6 to 59) and then TN conditions (20.9 ± 2.3 °C) until farrowing. Nine TN gilts and 12 HS gilts produced litters. At weaning (16.2 ± 0.4 d), mixed-sex piglets ( N = 160; 4.78 ± 0.15 kg body weight [BW ]) were transported (loading + transport + unloading) for 11 h 40 min. Following transport, piglets were blocked into pens ( n = 4 pigs/pen) by in utero and dietary treatments: in utero thermoneutral (IUTN ) + control (C ) diet ( n = 10 pens), IUTN + ND ( n = 10 pens), IUHS + C ( n = 10 pens), and IUHS + ND ( n = 10 pens). Treatment diets were fed from day 1 to 14 postweaning and transport (period 1 ), and the C diet was fed to all pigs from day 14 to 35 postweaning and transport (period 2 ). Production measures were taken in 7 d intervals to calculate average daily gain (ADG ), average daily feed intake (ADFI ), average daily net energy intake (ADEI ), gain:feed, and gain:net energy intake. Blood samples were collected prior to transport, following transport, and on days 2, 7, 14, 28, and 35 postweaning and transport to analyze cortisol, glucose, insulin, and nonesterified fatty acids. Behavior was assessed through video-recording on days 3, 5, 8, 11, and 13 postweaning and transport. In period 1, ADG was reduced ( P = 0.04; 20.0 g/d) in IUHS vs. IUTN pigs. Pigs fed ND diets had reduced ADFI ( P = 0.02; 9.3%) compared with C diet-fed pigs during period 1, which resulted in similar ADEI ( P = 0.23; 1, 115 ± 35 kcal/d). During transport, cortisol was decreased ( P = 0.03; 25.8%) in IUHS vs. IUTN pigs. On day 2, glucose was decreased ( P = 0.01; 13.8%) in IUHS vs. IUTN pigs. No in utero treatment-related behavior differences were observed but lying was reduced ( P = 0.03; 6.5%) and standing was increased ( P = 0.04; 14.1%) in ND vs. C pigs overall. In summary, IUHS reduced growth performance in pigs following weaning and transport, and providing an ND diet did not rescue the lost performance.